Digital literacy practices of novice English as a foreign language teacher in writing research articles for publication - Deiniatur, Much; Cahyono, Bambang Yudi (Intelektual Pustaka Media Utama, 2024)
Digital literacy is essential in writing research articles for publication in today's digital age, particularly for novice english as a foreign language (EFL) teacher trying to publish their research articles. This qualitative research explores the digital literacy practices of novice EFL teachers in writing research articles for publication, including the digital tools they use, their purposes for using these tools, and the challenges they face in using them. The data were collected using a questionnaire and interview. The study found that novice EFL teachers conceptualized digital literacy as the ability to search and evaluate credible online sources, using word processing and digital editing tools, collaborating online, and publishing their work digitally. Novice EFL teachers use various digital tools, such as word processing software, reference management software, and online academic databases, to improve their research and writing process. They use these tools for various purposes, such as collaborating with peers, improving their writing skills, and publishing their work online. However, novice EFL teachers face limited technical issues, limited access, inadequate technology infrastructure, and time management. It is recommended that academic institutions provide support to help novice EFL teachers develop their digital literacy skills, including technical support services, and training programs.